Diagnostic Accuracy of Contrast-Enhanced Ultrasonography for the Assessment of Small Renal Mass: A Prospective Study - Jae-Wook Chung; Seo Young Park; Seunghee Woo; Yun Ah Kim; Jun-Koo Kang; Yun-Sok Ha; Jun Nyung Lee; Bum Soo Kim; Tae-Hwan Kim; Ghil Suk Yoon; Tae Gyun Kwon; See Hyung Kim (Journal of Urologic Oncology)
Purpose We prospectively compared the diagnostic accuracy of kidney dynamic computed tomography (KDCT), magnetic resonance imaging (MRI), and contrast-enhanced ultrasonography (CEUS) for the assessment of small renal mass (SRM) (≤4 cm). Materials and Methods Seventy-six patients with SRM (mean age, 58.4±13.1 years) who underwent renal biopsy (n=11) or nephrectomy (partial or radical) (n=65) were enrolled. All patients underwent KDCT, MRI, and CEUS before renal biopsy or nephrectomy. Results The mean maximal tumor size was 21.0±9.8 mm. The mean R.E.N.A.L nephrometry score was 7.0±1.7. Fifty-six patients had renal cell carcinoma (RCC) (clear cell, 42; papillary, 7; chromophobe, 5; succinate dehydrogenase deficient, 1; unspecified RCC, 1). Twenty patients had a benign tumor (angiomyolipoma, 11; oncocytoma, 3; others, 6). Clinicopathologic variables were comparable in RCC and benign groups. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of KDCT were 89.3%, 10.0%, 73.5%, and 25.0%, respectively. The sensitivity, specificity, PPV, and NPV of MRI were 89.3%, 10.0%, 73.5%, and 25.0%, respectively. The sensitivity, specificity, PPV, and NPV of CEUS were 85.7%, 50.0%, 82.8%, and 55.6%, respectively. The diagnostic accuracy of KDCT, MRI, and CEUS were 68.4%, 68.4%, and 76.3%, respectively. In a subgroup analysis based on clinical tumor size of 10 mm and 20 mm, CEUS also showed the highest diagnostic accuracy. Conclusions CEUS had the highest specificity, PPV, and NPV and may help improve the assessment of SRM.